Smart Meters Rollout in Jordan: Opportunities, Business Models, Challenges, and Recommendations - Al-Salaymeh, Ahmed; AlTwassi, Sara; AlBeek, Rasha; Hassouneh, Kholoud; Athamneh, Diana; Alkiswani, Noor Eldin; Manna, Rashed; Asfour, Natalie (International Journal of Energy Economics and Policy, 2022)
Jordan’s energy demand is growing steadily due to many factors ranging from the growing population, to the needed energy for heating, cooling, desalination, and industry (Azzuni et al., 2020). EMRC has stated a new electricity tariff starting from April 2022. The high cost of electricity bill in Jordan with fixed tariff has resulted the need to have a dynamic tariff to transform energy use that lead to demand reductions, a shift in peak demand, a better management of distribution networks, in addition to reductions in operation costs. A full transition towards smart meters in Jordan is one of the main pillars to achieve a compatible smart grid system that will be a great solution to sustain the energy security. Also, it will lead to flatness the demand profile which will have economic consequences by reducing the cost of electricity generation. The current status of smart meters’ rollout, the optimal business model, challenges, and awareness towards energy strategies and smart meters deployment in Jordan have been investigated. It has been found that the optimal business model for the Jordanian market is a hybrid model of DGC and EaaS models. Also, a set of opportunities and recommendations have been concluded.